Construction of chevaux-de-frise from cellulose nanocrystals to enable mechano-bactericidal activity on recycled waste cotton films. Issue 3 (21st January 2022) - Zhou, Chufan; Girouard, François; O'Brien, Bridget; Ronholm, Jennifer; Wang, Yixiang
Abstract : The chevaux-de-frise-like nanostructure formed by CNC "needles" deposited on RC films through vacuum filtration can mechanically eliminate foodborne bacteria. Abstract : A chevaux-de-frise-like nanostructure is designed by depositing cellulose nanocrystals (CNCs) on regenerated cellulose (RC) films, both recycled from waste cotton fabrics, with the assistance of vacuum filtration to mechanically combat bacterial attachment and proliferation. The resultant all-cellulose films display rapid and significant bactericidal activity against Escherichia coli and Listeria monocytogenes .